CARACTERIZACIÓN DEL PERFIL DEL EMPRENDEDOR EN LAS PARROQUIAS RURALES DEL CANTÓN LOJA: PERIODO 2018 - Jimenez Ulloa, Andrea Del Carmen (2020)
As time goes by the word entrepreneurship has taken mainly force in society, it being necessary to emphasize this area, in order to continue generating job opportunities for the community, and avoid the great unemployment waves that faces the country nowadays. The present research allowed to analyze the entrepreneur’s profile of the rural parishes of Canton Loja, in order to determine their behavior in the business activity. The type of study used in this research is descriptive, the methodological design is not experimental; The research technique applied was the survey in which a questionnaire with closed questions was required and were directed to 374 entrepreneurs within the 13 rural parishes of Canton Loja. After having carried out the tabulation and got the results of the surveys, it is noted that the female sex is the one who takes the risk in order to undertake and excel in a competitive market, this is done from an age of 25 to 34 years, it can be highlighted that despite their economic limitations they have managed to complete their second level studies, looking for personal growth in order to succeed in their ventures, the main activities they perform are trade and service being the main source of income for their families. One of the factors that motivates them to undertake is the opportunity and need, this is because of the big economic changes that occur in the country. For most entrepreneurs, one of the principal motivations at the time to start a business was the advice they received from family, friends and 5 acquaintances, but for not having received training in their student life in terms of entrepreneurship leads to closure of your business resulting in a disappointing experience. Of the 374 interviewees, 5.1% adapt to the changes that are presented. That is why it is necessary to put more emphasis on the rural parishes of Canton Loja, in terms of entrepreneurship, helping them with training, facility of financial entities and re-governmental policies that encourage students with the idea of undertaking.